1997
DOI: 10.1023/a:1007420725704
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: In this study, we tested 137 Turkish children with cancer (51 with acute leukemia, 48 with lymphoma, 38 with solid tumors) while they were undergoing chemotherapy, and a control group of 45 for evidence of hepatitis B virus (HBV) and hepatitis C virus (HCV) infections using the enzyme-linked immunosorbent assay (ELISA) and polymerase chain reaction (PCR). The control group included children with other disease who had applied to the outpatient clinic during the study period and had no history of jaundice or tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…reported that a higher seroprevalence of HBV and HCV among paediatric patients with cancer (17). Topeli et al .…”
Section: Discussionmentioning
confidence: 99%
“…reported that a higher seroprevalence of HBV and HCV among paediatric patients with cancer (17). Topeli et al .…”
Section: Discussionmentioning
confidence: 99%
“…Yenice et al [11] uncovered a higher prevalence of anti-HCV relative to controls in patients with B-cell lymphoma and Hodgkin's lymphoma. Kocabaş et al [12] found a higher pervalence of HCV in patients with acute leukemia, lymphoma and solid tumors. However, Isikdogan et al [13] found no association in 119 NHL patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies on the role of HBV infection in lymphoproliferative diseases are limited, and relatively few of these have been conducted in Turkey. Altıntaş et al [24] and Kocabaş et al [12] revealed a higher prevalence of HBV in NHL and Hodgkin's lymphoma patients. In 1991, Olatunji et al [25] identified a higher prevalence relative to controls in Nigeria.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, anti HCV positivity was determined as 1.4%. In Turkey, HCV seroprevalence was reported as 4.5% in patients with thalassemia and sickle cell anemia who were receiving multiple transfusions, 5.8% in children with cancerincluding acute leukemia and 24.4% in children with hemophilia (19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%